2015
DOI: 10.1142/s0217732315500777
|View full text |Cite
|
Sign up to set email alerts
|

The spectral dimension in 2D CDT gravity coupled to scalar fields

Abstract: Causal Dynamical Triangulations (CDT) provide a non-perturbative formulation of Quantum Gravity assuming the existence of a global time foliation. In our earlier study we analyzed the effect of including d copies of a massless scalar field in the two-dimensional CDT model with imaginary time. For d > 1 we observed the formation of a "blob", somewhat similar to that observed in four-dimensional CDT without matter. In the two-dimensional case the "blob" has a Hausdorff dimension D H = 3. In this paper we study t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…This expected behavior seems to be matched by the results of very recent 2D Monte-Carlo simulations of CDT coupled to more than one massive scalar field [106][107][108]. It was found that, above a certain value of their mass, the dynamics of the CDT+matter system is significantly different from the massless case.…”
Section: Jhep02(2016)167supporting
confidence: 76%
“…This expected behavior seems to be matched by the results of very recent 2D Monte-Carlo simulations of CDT coupled to more than one massive scalar field [106][107][108]. It was found that, above a certain value of their mass, the dynamics of the CDT+matter system is significantly different from the massless case.…”
Section: Jhep02(2016)167supporting
confidence: 76%
“…To bridge the gap towards particle-physics phenomenology, the inclusion of matter fields could be fruitful, and has been explored, e.g., in [256,257]. In the related Euclidean dynamical triangulations approach, gauge fields were studied early on [258] and fermionic matter fields have been introduced [259], with first indications that chiral symmetry -protecting the lightness of fermions compared to the Planck scale -could remain intact, similarly to the continuum approach to asymptotic safety [28].…”
Section: Causal Dynamical Triangulationsmentioning
confidence: 99%
“…The results can be contrasted with EDT, where matter does not seem to influence the geometry in a significant way [45,46,47,48,49]. In two-dimensional CDT models, adding a coupling to scalar [89,90,91,92,93] and gauge [94] fields did result in a notable change of the geometry, as described in the articles cited. However, no substantial impact of scalar field on spacetime geometry or the phase diagram was shown in four-dimensional CDT in studies previous to the articles on which this chapter is based.…”
Section: Dynamical Scalar Fieldsmentioning
confidence: 97%